Cardiac phenotypes in the acute-phase of microscopic polyangiitis involves dilatation of the left atrium caused by LV diastolic dysfunction. (14th October 2021) - Kinoshita, N; Nawata, T; Okuda, S; Kubo, M; Wada, Y; Kobayashi, S; Tanaka, N; Yano, M
Abstract: Background: Microscopic polyangiitis (MPA) is a type of primary systemic vasculitis that affects various organs, especially the lungs and kidneys. However, few reports regarding cardiac features of MPA patients were found. Purpose: We aim to investigate the echocardiographic parameters of acute-phase MPA. Methods and results: This single-center retrospective study included 15 patients with MPA (Mean age at 72.2±7.1 years, women 73.3%) who underwent echocardiography within two weeks of commencing steroid therapy for induction or reinduction. The echocardiography parameters of the patients were compared with those of 30 age and sex-matched controls. In the MPA group, the commonly affected organs were kidneys (93.3%) and lungs (46.7%); 5 patients (33.3%) had a history of hypertension, which had a similar frequency as the control group. No significant difference in left ventricular (LV) diameter, LV ejection fraction, e', or inferior vena cava diameter was observed between the two groups. However, the MPA group showed significantly higher left atrial (LA) diameter (p=0.033) and LA volume index (p=0.001), as well as higher early diastolic filling velocity (E-wave, p=0.015; E/A, p=0.043; E/e', p=0.041), diastolic pulmonary venous flow velocity (p=0.013), trans-tricuspid pressure gradient (p=0.019), and shorter deceleration time (p=0.038), associated with mildly thicker ventricular walls of left ventricle (LV) than the control group. Moreover, serum levels of C-reactive protein showed significant correlation between E wave (r=0.58, p=0.023), E/A (r=0.67, p=0.006), and deceleration time (r=−0.69, p=0.005) in the MPA group. These results may indicate that in MPA, increased LV stiffness, rather than impairment of LV relaxation was contributed to LV diastolic function, resulting in LA enlargement. Conclusion: Patients with acute-phase MPA had LA dilatation associated with LV diastolic dysfunction. This finding indicates the importance of cardiac assessment in patients with MPA. FUNDunding Acknowledgement: Type of funding sources: None.